Spatiotemporal Insights Into RNA–Organelle Interactions in Neurons - Kharod, Shivani C.; Hwang, Dong-Woo; Das, Sulagna; Yoon, Young J. (Frontiers in Cell and Developmental Biology, 2021)
Neurons exhibit spatial compartmentalization of gene expression where localization of messenger RNAs (mRNAs) to distal processes allows for site-specific distribution of proteins through local translation. Recently, there have been reports of coordination between mRNA transport with vesicular and organellar trafficking. In this review, we will highlight the latest literature on axonal and dendritic local protein synthesis with links to mRNA–organelle cotransport followed by emerging technologies necessary to study these phenomena. Recent high-resolution imaging studies have led to insights into the dynamics of RNA–organelle interactions, and we can now peer into these intricate interactions within subcellular compartments of neurons.